PERBERDAYAAN POSYANDU LANSIA UNTUK MENINGKATKANKUALITAS HIDUP LANSIA DI RW.07 KELURAHAN MAGERSARI KABUPATEN SIDOARJO - Wijaya, I Nyoman; I Nyoman Wijaya; Abdul Rahem; Gusti Noorrizka V; Yuni Priyandani; Neny Purwitasari; Umi Athiyah; Andi Hermansyah; Yunita Nita; Ana Yuda; Arie Sulistyarini; Bambang Subakti Z (Jurnal Bakti untuk Negeri, 2025)
An elderly person is someone who has reached the age of 60 years and above. From a health perspective, the elderly will experience an aging process characterized by a decrease in physical endurance, making them susceptible to disease. Based on the problem of the elderly in Sidoarjo not understanding healthy lifestyles, how to manage medication has the potential to decrease the quality of life of the elderly. Therefore, it is necessary to empower the elderly through training to improve the quality of life of the elderly. This community service activity targets the category of Sustainable Development Goals (SDGs), namely SDGs 3, which is ensuring a healthy life and improving the welfare of all residents of all ages. The empowerment activity was carried out at the RW.07 Hall, Magersari Village, Sidoarjo District on Saturday, June 28, 2025. Attended by 90 elderly people. The activity began with morning exercise, providing material and demonstrations on making herbal medicine, providing material on infectious diseases (TB) and degenerative diseases (DM and hypertension), providing material on how to properly manage medication and ending with a post-test. The results of the activity showed that the elderly were very enthusiastic about participating in the entire series of activities. The increase in elderly knowledge was seen from the increase in post-test scores. The paired-sample statistical test results yielded a P-value of 0.000. This indicates a significant difference between the pre-test and post-test results. Participants' understanding improved both before and after the educational material was provided.